Indonesia's Middle-Power Diplomacy amid U.S.–China Strategic Competition: Domestic Politics and Foreign Policy Transformation - Putri Azzahra Nirmala (Artes Libres Institutum, 2026)
The intensifying strategic rivalry between the United States and China has fundamentally reshaped the geopolitical landscape of the Indo-Pacific, placing middle powers under increasing pressure to navigate competing political, economic, and security interests. Indonesia has responded by reinforcing its long-standing